2018
DOI: 10.3390/genes9090427
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variants in pre-miR-146a, pre-miR-499, pre-miR-125a, pre-miR-605, and pri-miR-182 Are Associated with Breast Cancer Susceptibility in a South American Population

Abstract: Breast cancer (BC) is one of the most frequent tumors affecting women worldwide. microRNAs (miRNAs) single-nucleotide polymorphisms (SNPs) likely contribute to BC susceptibility. We evaluated the association of five SNPs with BC risk in non-carriers of the BRCA1/2-mutation from a South American population. The SNPs were genotyped in 440 Chilean BRCA1/2-negative BC cases and 1048 controls. Our data do not support an association between rs2910164:G>C or rs3746444:A>G and BC risk. The rs12975333:G>T is monomorphi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 94 publications
1
23
0
Order By: Relevance
“…Rs2043556 was located in pre-miR-605 and our study showed that this SNP was associated with differential expression of mature miR-605 (including miR-605-3p and miR-605-5p), consistent with the study by Zhou et al (2017) Pre-miR-605 had previously been linked to a number of malignancies, such as prostate cancer, breast cancer (Morales et al, 2018), non-small-cell lung cancer (Zhou and Li, 2019), and oral squamous cell carcinoma (Miao et al, 2016), suggesting its potential as a biomarker for cancer. Interestingly, tooth agenesis and cancer development share common molecular pathways and previous study found that almost all types of tumors were more common in families with tooth agenesis (Kuchler et al, 2013).…”
Section: Discussionsupporting
confidence: 90%
“…Rs2043556 was located in pre-miR-605 and our study showed that this SNP was associated with differential expression of mature miR-605 (including miR-605-3p and miR-605-5p), consistent with the study by Zhou et al (2017) Pre-miR-605 had previously been linked to a number of malignancies, such as prostate cancer, breast cancer (Morales et al, 2018), non-small-cell lung cancer (Zhou and Li, 2019), and oral squamous cell carcinoma (Miao et al, 2016), suggesting its potential as a biomarker for cancer. Interestingly, tooth agenesis and cancer development share common molecular pathways and previous study found that almost all types of tumors were more common in families with tooth agenesis (Kuchler et al, 2013).…”
Section: Discussionsupporting
confidence: 90%
“…The reference list of these records were also hand-searched to identify additional studies. Ultimately, 12 records (which comprised 13 studies) were included in the meta-analysis 15,16,[24][25][26][27][28][29][30][31][32][33] . We also included preliminary data from our laboratory in the meta-analysis, making the total number of included studies 14.…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies have examined the association of the polymorphism with breast cancer susceptibility, but the results obtained have been inconsistent. For instance, while He et al 15 demonstrated that the variant allele of MIR499A rs3746444 polymorphism was significantly associated with an increased susceptibility to breast cancer, Morales et al 16 did not find any significant association. One of the major reasons for the inconsistency of study results in genetic association studies is the limited sample size and thus, low statistical power of the individual studies 17,18 .…”
mentioning
confidence: 99%
“…By way of illustration, the mutations in the BRCA1/2 genes are responsible for an average risk of 16-20% for hereditary breast cancer. Recent research, however, has produced evidences to support the role microRNAs (miRNAs) play in development and progression of breast cancer (Morales et al, 2018). The human genome encodes more than 1,000 miRNAs (Wang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%